Evolution of iodine deficiency disorders control program in India: A journey of 5,000 years - Chandrakant S Pandav (Wolters Kluwer Medknow Publications, 2013)
Iodine deficiency disorders (IDD) has been documented since around 5,000 years. However, geological factors like frequent glaciations, flooding, and changing of course of rivers has led to iodine deficiency in soil. As a result everyone remains at risk of IDD, if optimum intake of iodine is not sustained. Evolution of the IDD control program in India has been a dynamic process. The model of IDD control program in India provides important lessons for successful implementation of a national health program. In formulating National Health Programs; policy environment, scientific inputs, political will, and institutional structure for decision making are necessary but not sufficient. Continuous and dynamic generation of reliable and representative state and national level data, proactive recognition of values of key stakeholders and addressing them through sustained advocacy, development of partnerships among stakeholders, institutional continuity, and mentorship are critical for achieving sustainability of results.